Global media spectacle : news war over Hong Kong - Li, Jinquan, 1946- (SUNY series in global media studies., 2002)
An interdisciplinary group of scholars, all with some background in journalism, attempt to demonstrate now nation-states fight an "international discursive battle via the media to compete for legitimacy and recognition." They use the 1997 transfer of sovereignty of Hong Kong as a case study, interweaving interviews with international journalists, content analysis, and discourse analysis of elite newspapers and television networks from eight countries or regions. Annotation copyrighted by Book News, Inc., Portland, OR